The Influence of Feature Completeness, Ease of Use and Convenience of Digital Products on Customer Loyalty of PT Bank NTB Syariah Mobile Banking Users with Self-Efficacy as a Moderating Variable - Akbar Aditya Maulana; Akhmad Saufi; Dwi Putra Buana Sakti (Cita Konsultindo Research Center, 2024)
This research aims to examine the influence of feature completeness, digital product convenience, and digital product convenience on customer loyalty of PT mobile banking users. Bank NTB Syariah with self-efficacy as a moderating variable. The sampling technique used the Slovin formula to obtain a sample of 395 Bank NTB Syariah customers (respondents). The statistical tool used in the research is SEM-PLS version 3.0. Data analysis techniques use descriptive statistics, outer model testing, inner model testing, and hypothesis testing. The results of this research show that the completeness of features directly and partially has a negative and insignificant influence on customer loyalty of Bank NTB Syariah mobile banking users; The ease of use of mobile banking directly and partially has a positive and significant influence on the loyalty of customers using Bank NTB Syariah mobile banking; The convenience of mobile banking products directly and partially has a positive and significant influence on customer loyalty of Bank NTB Syariah mobile banking users; Self-efficacy weakens the influence of feature completeness on customer loyalty; Self-efficacy does not moderate the effect of ease of use on customer loyalty; and Self-efficacy does not moderate the effect of product convenience on customer loyalty.